Generation of a photovoltaic system as an alternative to the traditional electrical distribution network - Ruiz, Huber Quispe (2022)
The objective of this research is to determine whether a photovoltaic system is more beneficial than a traditional electrical grid system for households with high energy consumption in the district of Paiján. It was considered a quantitative approach, applied type, non-experimental - transversal design and descriptive scope given that a comparison was made between the two variables to know the differences between both groups. It was carried out in a house with the installation of a photovoltaic system, making use of observation and documentary analysis techniques. The result of the research was that the photovoltaic system is more beneficial in terms of photovoltaic generation and traditional electricity distribution variables because it contributes to environmental protection, it is also a technology that is growing rapidly and does not generate maintenance and consumption costs, except for those generated in the acquisition of materials and installation. Finally, it was concluded that a photovoltaic generation system is the main renewable technology that is significantly reducing its costs, so that they are already very competitive with conventional ones in a growing number of installations.